2012
DOI: 10.1093/jnci/djs136
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Reduced Tobacco Smoking on Lung Cancer Mortality in the United States During 1975–2000

Abstract: BackgroundConsiderable effort has been expended on tobacco control strategies in the United States since the mid-1950s. However, we have little quantitative information on how changes in smoking behaviors have impacted lung cancer mortality. We quantified the cumulative impact of changes in smoking behaviors that started in the mid-1950s on lung cancer mortality in the United States over the period 1975–2000.MethodsA consortium of six groups of investigators used common inputs consisting of simulated cohort-wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
115
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 151 publications
(116 citation statements)
references
References 23 publications
0
115
0
1
Order By: Relevance
“…This might be explained that there were many lung cancer patients included in NCRC-LM. As known to all, lung cancer is a disease closely associated with smoking (Moolgavkar et al, 2012;Rosenberg et al, 2012). Otherwise, alcohol consumption was found different between CRC groups with and without liver metastasis.…”
Section: Discussionmentioning
confidence: 89%
“…This might be explained that there were many lung cancer patients included in NCRC-LM. As known to all, lung cancer is a disease closely associated with smoking (Moolgavkar et al, 2012;Rosenberg et al, 2012). Otherwise, alcohol consumption was found different between CRC groups with and without liver metastasis.…”
Section: Discussionmentioning
confidence: 89%
“…Tobacco smoking is an undisputed carcinogen of lung cancer. Recent study also found its relation with cancers in other organs including esophagus, pancreas, stomach, liver, kidney and even uterine cervix (31). Although the burden of lung cancer is heavy worldwide, it is one of the most preventable cancers.…”
Section: Discussionmentioning
confidence: 96%
“…Current trend of increasing smoking prevalence in developing countries (Giovino et al, 2012), would result in higher mortality in these countries in near future (Peto et al, 2001;Jha et al, 2008). In this context, tobacco control efforts targeted at cessation of smoking behavior has bearing on smoking attributable deaths including cancer mortality (Coambs et al, 1989;Jha et al, 2009;Moolgavkar et al, 2012). Experience from developed nations suggest that such intervention helped light smokers to quit with decreased prevalence of tobacco use, but also caused hardening of remaining smokers over time (Emery et al, 2000;Warner et al, 2003;Hughes, 2011).…”
Section: Introductionmentioning
confidence: 99%